"Saving Face": An Online Study of the Injecting Use of DIY Botox and Dermal Filler Kits. Issue 3 (August 2018) - Brennan, Rebekah; Wells, John S. G.; Van Hout, Marieclaire
This study reports on an empirically underdocumented practice in contemporary aesthetic enhancement culture, the self-injection of unregulated DIY Botox and dermal filler kits purchased online. Data were collected from 4 online discussion forums containing disclosures in relation to use of DIY kits and analyzed using ethnographic content analysis. Motivation to source DIY Botox and dermal fillers online was grounded in desire to avoid financial cost of professional services and a lack of confidence in practitioners. Future intentions to order online raw materials and "formulas" to prepare dermal fillers at home were expressed. Individuals taught themselves to inject through watching YouTube tutorials and downloading Botox injection maps from the Internet. Although individuals demonstrated awareness of the health risks involved with self-injection of unregulated products, this was not a deterrent. Future research is warranted to document the injecting practices and health outcomes of individuals who inject DIY Botox and dermal filler kits to inform targeted harm reduction interventions by health-care practitioners.